Fortsetzung erfolgreicher Versuche in der Stellnetzfischerei auf Steinbutt - Steinberg, R.; Mentjes, Tönjes (1987)
Johann Heinrich von Thunen-Institute, Federal Research Institute for Rural Areas, Forestry and Fisheries began publishing the Informationen aus der Fischereiforschung – Information on Fishery research in 2010